Alimentação de terreiro na periferia de Belém: uma encruzilhada entre comidas sagradas e comidas do cotidiano - AGUIAR, Valéria Cristina da Silva (2023)
In this work, we tried to highlight the Afro-Brazilian culture, highlighting its importance and resistance in the construction of Brazilian and regional cuisine. Expressing, briefly, how the racist structure affects an Afro-Brazilian religion today, in addition, presenting how food can be a link between food from umbanda terreiros and “common” cuisines, in an attempt to reduce distance and discrimination, for this it was carried out through interviews pre-established dishes that are offered and consumed inside the house from the choice of its ingredients, its preparation, symbology to what is served to the public that are common dishes for society.